Are SADI-S and BPD/DS bariatric procedures identical twins or distant relatives? – A case report. Issue 2 (March 2023) - Guimarães, Marta; Pereira, Ana Marta; Pereira, Sofia S.; Almeida, Rui; Lobato, Carolina B.; Hartmann, Bolette; Holst, Jens J.; Nora, Mário; Monteiro, Mariana P.
Abstract: Given the common anatomical features and similar short-term weight loss outcomes, Biliopancreatic Diversion with Duodenal Switch (BPD/DS) and Single-Anastomosis Duodenoileal bypass with Sleeve gastrectomy (SADI-S) are considered identical bariatric procedures, apart from technical complexity being lower for SADI-S. In the absence of prospective randomized trials or long-term comparative studies the rationale for choosing between procedures is hampered. Post-bariatric hormonal profiles could contribute to understand the underlying mechanisms and potentially be used as a decision aid when choosing between procedures. The main aim of this study was to compare the outcomes of BPD/DS and SADI-S, in genetically identical individuals exposed to similar environmental factors. Two identical twin (T) female patients, one submitted to BPD/DS (T_BPD/DS) and another to SADIS-S (T_SADI-S) were followed up to one year after surgery. Before surgery and at 3, 6 and 12 months after surgery, both patients underwent mixed meal tolerance tests (MMTT) to evaluate postprandial glucose, glucagon and GLP-1 response. In addition, 3 months after surgery, glucose dynamics were assessed using a Flash Glucose Monitoring (FGM) system for 14 days. The percentage of total weight loss (%TWL) was higher for T_BPD/DS compared to T_SADI-S (34.03 vs 29.03 %). During MMTT, T_BPD/DS presented lower glucose, glucagon, insulin and C-peptide excursions at all timepoints when compared to SADI-S; along with a greater percentage of time within the low glucose range (55.97 vs 39.93 %) and numerically lower glucose variability indexes on FGM (MAG change:0.51 vs 0.63 mmol/l×h −1 ). In patients with the same genetic background, BPD/DS was shown to result in greater weight loss than SADI-S. The differences in glucose and enteropancreatic hormone profiles observed after BPD/DS and SADI-S suggest that different mechanisms underlie weight loss. Highlights: BPD/DS achieves greater weight loss than SADI-S. BPD/DS results in lower glycemic variability when compared to SADI-S. BPD/DS and SADI-S elicit different intestinal and pancreatic hormone profiles. Data suggests that BPD/DS and SADI-S may involve different weight loss mechanisms.